Phenotypic and genotypic characterization of basil hybrids and cultivars - Alea Dayane Dantas de Santana; Arie Fitzgerald Blank; Maria de Fátima Arrigoni-Blank; Thiago Matos Andrade; Mércia Freitas Alves; Juliana Oliveira de Melo; Péricles Barreto Alves (Bioscience Journal, 2018)
This study aimed to evaluate the phenotypic and genotypic performance of basil (Ocimum basilicum L.) hybrids and cultivars, grown in four crop years, in the municipality of São Cristóvão, state of Sergipe. The following variables were evaluated: dry weight of aerial part; essential oil content and yield; and the contents of linalool, 1,8-cineol, neral, geranial, and methyl cinnamate. Five hybrids ('Sweet Dani' x 'Maria Bonita', 'Genovese' x 'Maria Bonita', 'Cinnamon' x 'Maria Bonita', 'Sweet Dani' x 'Cinnamon', and 'Sweet Dani' x 'Genovese') and four parent cultivars ('Maria Bonita', 'Sweet Dani', 'Genovese', and 'Cinnamon') of basil were evaluated. The essential oils were obtained from dried leaves by hydrodistillation. The chemical composition of essential oils was analyzed by GC/MS-FID. Means were clustered, and the genetic and phenotypic parameters were estimated. Linalool was the main compound of most genotypes. Hybrids 'Cinnamon' x 'Maria Bonita', 'Sweet Dani' x 'Cinnamon', and 'Sweet Dani' x 'Maria Bonita' had methyl cinnamate (41.93 %), methyl cinnamate (60.15 %), geranial (15.20 %), and neral (11.46 %), respectively, as major compounds. The sources of variation were significant at the 1 % probability level, according to the F tests for all variables, confirming the differences in the performance of genotypes in the different years. Most of the variation among the studied variables resulted from the genetic variation.